Jethro and the Jews : Jewish biblical interpretation and the question of identity - Lawrence, Beatrice J. W. (The Brill Reference Library of Judaism, 2017)
In Jethro and the Jews , Beatrice J. W. Lawrence examines rabbinic texts that address the biblical character of Jethro, a Midianite priest, Moses' advisor and father-in-law, and the creator of the system of Jewish jurisprudence. Lawrence explores biblical interpretations in Midrash, Targum and Talmud, revealing a spectrum of responses to the presence of a man who straddles the line between insider and outsider. Ranging from character assassination to valorization of Jethro as a convert, these interpretive strategies reveal him to be a locus of anxiety for the rabbis concerning conversion, community boundaries, intermarriage, and non-Jews.